Security issues for the Internet and the World Wide Web - Cameron, Debra (Computer Technology Research Corp. CharlestonUS, 1997)
Seeks to assist management in deciding how to address the issue of Internet security and to determine what security approaches provide the best means to service the unique needs of each organization.